Palladium-catalyzed dual C–H or N–H functionalization of unfunctionalized indole derivatives with alkenes and arenes - Broggini, Gianluigi; Beccalli, Egle M.; Fasana, Andrea; Gazzola, Silvia (Beilstein Journal of Organic Chemistry, 2012)
This review highlights the development of palladium-catalyzed C–H and N–H functionalization reactions involving indole derivatives. These procedures require unactivated starting materials and are respectful of the basic principle of sustainable chemistry tied to atom economy.
Keywords: alkenylation; arylation; C–H functionalization; indoles; N–H functionalization; Pd catalysis